2017
DOI: 10.1016/j.jclepro.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Parametric experimental study and design of experiment modelling of sapphire grinding

Abstract: a b s t r a c tThis study investigates and models the grinding process of single crystal sapphire. Five parameters: the wheel speed, the feed speed, the vertical feed, the ultrasonic assistance and the crystallographic direction were considered via a design of experiments (DoE) approach. The responses were multiple but can be divided in three groups: the process, the machine and the grinding quality. DoE results revealed that the parameters interact in a complex manner and depends on the responses. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Griffiths et al (2016) consider 3D printed products for the environmental and economic assessment at the design stage for the part optimization using DOE. Wasmer et al (2017) study a parametric experiment for sapphire grinding under multiple responses. Lujan-Moreno et al (2018) tune hyperparameters through a random forest case study and demonstrate the use of DOE and RSM under a machine learning algorithm.…”
Section: Dynamic Coal Blendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffiths et al (2016) consider 3D printed products for the environmental and economic assessment at the design stage for the part optimization using DOE. Wasmer et al (2017) study a parametric experiment for sapphire grinding under multiple responses. Lujan-Moreno et al (2018) tune hyperparameters through a random forest case study and demonstrate the use of DOE and RSM under a machine learning algorithm.…”
Section: Dynamic Coal Blendingmentioning
confidence: 99%
“…(2016) consider 3D printed products for the environmental and economic assessment at the design stage for the part optimization using DOE. Wasmer et al . (2017) study a parametric experiment for sapphire grinding under multiple responses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Performance prediction of any machining process such as surface roughness, material removal, depth of cut, etc. could be modelled [171][172][173] using ML techniques by correlating to machining parameters and sensor data as shown in Fig. 26 Fig.…”
Section: Modelling Of the Finishing Processmentioning
confidence: 99%
“…31 This study preliminarily stated the influence of crack orientation on the machined surface roughness for different crystal planes of sapphire. Furthermore, Wasmer et al 32 conducted parametric experiments on A-plane of sapphire and found that grinding along the c -axis suffers a reduced grinding force compared with that along the m -axis. Mohammadi and Patten 33 investigated the effect of crystal orientation and laser power on the BDT depth of sapphire by laser-assisted scratching tests, and it is confirmed that different crystal orientations on C-plane have different BDT depths no matter with or without laser assist.…”
Section: Introductionmentioning
confidence: 99%